Subnanomolar detection of tuberculosis biomarker MPT64 in sandwich sers immunoassay on novel low -cost substrate - Ralchenko, Y.; Khamkhash, L.; Bukasov, R. (Nazarbayev University, 2014)
The use of SERS for detection, analysis and imaging has attracted great interest in the past decade owing to its high sensitivity and molecular fingerprint specificity. There is an increasing interest in scientific community to SERS as it becomes a versatile method for early medical diagnostics and reliable detection of major health threats to humans (e.g. cancer, tuberculosis, etc) and animals [1]. The key component of our SERS-based immunoassay include:1) a capture substrate to specifically adsorb antigens from solution; (2) Extrinsic Raman Labels (ERLs): surface functionalized gold nanoparticles (AuNPs) to bind to captured antigens selectively and generate intense SERS signals, which contain both capture antigen and SERS active readout molecule (4-nitrobenzenethiol (4-NBT)).
Keywords: subnanomolar detection; tuberculosis biomarker; antibodies; molecule